Does Good Governance Spur Economic Growth Outside the Hydrocarbon Sector? Empirical Evidence from Algeria (2002-2017) - Hanaa, Benazza (European Scientific Journal, ESJ, 2019)
The current study aims to investigate the impact of good governance variables on economic growth outside hydrocarbon sector (Real GDP growth in all other sectors except hydrocarbon) in Algeria, based on annual time series data over (2002-2017) using the (ARDL) approaches. The results show the significant effect of control corruption index(CC),and government effectiveness index(GE) on economic growth in Algeria in both short and long run ,while there is the absence of any significant effect of rule of law index(RL) on economic growth neither in the short nor long run.